Liquidus curve of uranium–plutonium mixed oxide (MOX) system - Leonid Burakovsky; Dean L. Preston; Andrew A. Green (Frontiers in Nuclear Engineering)
Mixed oxides of uranium and plutonium (MOX) are currently considered reference fuels for the new generation of fast breeder reactors such as ASTRID. The key factor determining the performance and safety of fuel such as MOX is its operational limits in applied practice, which are closely related to the material’s structure and thermodynamic stability. They are, in turn, closely related to the ambient (zero pressure) melting point (Tm); thus, Tm is an important engineering parameter. However, the current knowledge of Tm of MOX is limited and controversial, as several reported studies do not converge on the unique behavior of Tm as a function of x. In this study, we present a theoretical model for the melting curve (liquidus) of a mixture and apply it to MOX considered a mixture of pure UO2 and PuO2. The model uses the known melting curves of pure constituents as an input and predicts the melting curve of their mixture. It has only one free parameter, which must be determined independently. In the case of MOX, Tm of MOX as a function of x as given by the model has a local minimum at x≈0.64, which disagrees slightly with our previous ab initio molecular dynamics studies that place this minimum at x=0.7.